Historical Perspective of the Triple Nexus: The Challenges of Humanitarian, Peacebuilding, and Development Activities - Ozkul, Abdullah Onder (European Scientific Journal, ESJ, 2021)
This paper focuses on discussing development, humanitarian aid, and peace-making notions alongside their historical backgrounds. Different development approaches and methodological dimensions of development were examined through the development process of Turkey. Humanitarian aid was also handled from a historical perspective. The natural and manmade disasters that humanity has faced in recent years and the performed humanitarian interventions were examined. The interaction points for humanitarian aid, development, and the concept of Triple Nexus, a new concept that meets this process, were also examined. According to the chronology of notions, this study first examines the concept of development with the literature research method, and then the literature research results on the concept of humanitarian aid were included. Descriptive research and observation methods, which are among qualitative research methods, were applied in this paper holistically.